Kelor Leaves Infusion as a Alternative in Increasing the Volume of Breastmilk and Birth Weight in Newborn - Diah Evawanna Anuhgera; Nikmah Jalilah Ritonga; Riris Sitorus (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Background: An increase in the volume of breast milk and baby weight is the hope of every mother during breastfeeding. The consistency and quality of breastfeeding is determined by a mother. Moringa leaves, which is a typical plant in Indonesia, have many benefits, especially to increase milk production and nutrition for infants and children in the growth process. The purpose of this study was to determine the effect of morinaga leaves in increasing the volume of breast milk and birth weigh of babies. Method:The design of this study was quasy eksperimental studies with purposive sampling with inclusion criteria. The sample in this study were all breastfeeding mothers on the first postpartum day as many as 30 people. In this study there were two groups, namely the control group and the intervention group. The instruments in this study were Moringa leaves, measuring cups, electric breast pumps, and baby scales and observation sheets. Data analysis used is paired and unpaired t-test. Result:The results showed that there was a difference between before and after the administration of Moringa leaves in the intervention group of 38.95 ml, while in the control group it was 16.1 ml. The baby's weight gain in the intervention group was 585 grams. Statistical results showed that giving Moringa leaves was effective on breast milk volume and infant weight with a significance value of p = 0.00 while in the control group there was a difference in the increase in breast milk volume with p = 0.000 but there was no significant difference in the baby weight variable with a value of p = 0.651. Conclusion: Moringa leaves infusion can be used as an alternative therapy to increase the volume of breast milk and baby weight in the breastfeeding process. Specialized health workers for midwives can assist mothers in educating postpartum mothers in consuming steeped Moringa leaves to increase breast milk and baby weight and support the success of exclusive breastfeeding